Geothermal Gradient Drilling and Measurements Ascension Island, South Atlantic Ocean - Sibbett, B. S.; Nielson, D. L.; Adams, M. C. (Geothermal Energy Program (U.S.), 1984)
This technical report on the Phase II geothermal exploration of Ascension Island documents the data collected during thermal gradient drilling and the subsequent thermal and fluid chemical investigations. It also documents the completion of the Phase II exploration strategy which was proposed at the end of the Phase I--Preliminary Examination of Ascension Island. The thermal gradient drilling resulted in seven holes which range from 206 to 1750 ft (53-533 m) deep, with a cumulative footage of 6563 ft (2000 m). The drilling procedure and the problems encountered during the drilling have been explained in detail to provide information valuable for any subsequent drilling program on the island. In addition, the subsurface geology encountered in the holes has been documented and, where possible, correlated with other holes or the geology mapped on the surface of the island. Temperatures measured in the holes reach a maximum of 130 F (54.4 C) at 1285 ft (391.7 m) in hole GH-6. When the temperatures of all holes are plotted against elevation, the holes can be classed into three distinct groups, those which have no thermal manifestations, those with definite geothermal affinities, and one hole which is intermediate between the other two. From consideration of this information, it is clear that the highest geothermal potential on the island is in the Donkey Flat area extending beneath Middleton Ridge, and in the Cricket Valley area. Because of the greater drilling depths and the remote nature of the Cricket Valley area, it is recommended that future exploration concentrate in the area around Middleton Ridge.